Tough monolithic TiO2 materials fabricated by the sol-gel process accompanied with phase separation in solutions of SiC nanofibers and preceramic polymers. (March 2023) - Xu, Xin; Hu, Hongli; Zhong, Hangyu; Wang, LinGe; Zhang, Bo-xing
Abstract: In recent decades, the sol-gel process accompanied with phase separation has been employed to fabricate porous monolithic ceramic materials. However, it is challenging to obtain crack-free samples by using this method, due to the fragile nature of porous ceramic materials and the large internal stress generated from drying and calcination process. In this work, tough monolithic titania (TiO2 ) materials were fabricated by the sol-gel process accompanied with phase separation in solutions of silicon carbide (SiC) nanofibers and preceramic polymers. It was found that polyethylene oxide (PEO) and ethylenediamine (EDA) can promote phase separation and sol-gel process respectively, and the micro-morphology of porous monolithic TiO2 materials can be flexibly tuned by adjusting the contents of PEO and EDA. The addition of SiC nanofibers effectively enhanced the mechanical performance and photocatalytic activity of porous TiO2 materials without altering their bicontinuous micro-morphology. Taking TiO2 materials as an example, this work demonstrates a novel methodology to fabricate ceramic nanofibers reinforced porous monolithic ceramic materials. Graphical abstract: SiC nanofibers strengthened monolithic TiO2 materials were fabricated by the sol-gel process accompanied with phase separation in solutions of SiC nanofibers and preceramic polymers. The introduction of SiC nanofibers can effectively overcome the fragility of porous TiO2 materials and enhance photocatalytic activity by means of coupling effects. Image, graphical abstract